Study of the knowledge, attitude and practice on occupational safety and health risk among sme(s) workers in Selangor Malaysia - Aisya Nadirah, Abdul Jamil (2024)
Occupational Safety and Health (OSH) is an important field that addresses the safety, health, and welfare of workers across the various types of industries. It is widely used by Malaysian companies and industries since it is one of the requirements outlined in the Occupational Safety and Health Act (OSHA) 1994. Despite that, it has been said that OSH implementation in Small and Medium Enterprise (SMEs) is insignificant due to their small workforce. However, there are high occupational accidents found to be caused by the SME sector. This study was conducted in order to assess the knowledge, attitudes, and practices (KAP) on OSH risk among SMEs workers in Selangor, Malaysia before analyzing the data using SPSS version 25.0 to determine the associations between knowledge, attitudes, and practices in OSH risk. A cross-sectional study was conducted using a quantitative method where a self-report survey of five-point Likert scale was used for a total of 105 workers coming from service and manufacturing sector in SMEs. Descriptive statistic shown a moderate to strong level of KAP while Spearman correlation, show a significant positive relationship shown between KAP level which suggesting workers with higher safety knowledge and positive attitudes are more likely to conduct safer work practices.